Genomic Investigations into Acute Inflammatory Lung Injury - Garcia, Joe G. N. (American Thoracic Society, 2011)
Acute lung injury (ALI) and its more severe form, acute respiratory distress syndrome, are complex illnesses involving the interplay of both environmental (such as mechanical ventilation) and genetic factors. To understand better the underlying mechanisms of pathogenesis associated with ALI, we recently identified several candidate genes by global expression profiling in preclinical models of ALI and relevant single-nucleotide polymorphisms. We summarize here several strategies successfully used to identify novel ALI candidate genes and detail the validation of variants in these genes as contributing factors to ALI pathobiology, conclusions based on functional analyses, and specific genetic association studies conducted in ALI cohorts. Continued insights into ALI pathogenesis and identification of genetic variants, which confer ALI risk and severity, promise to reveal novel molecular therapeutic targets that can be translated into personalized treatments to reduce the very high, unacceptable mortality of this disorder.